2015
DOI: 10.1111/ina.12216
|View full text |Cite
|
Sign up to set email alerts
|

Moisture damage in home associates with systemic inflammation in children

Abstract: This study investigated the association between confirmed moisture damage in homes and systemic subclinical inflammation in children. Home inspections were performed in homes of 291 children at the age of 6 years. Subclinical inflammation at the age of 6 years was assessed by measuring the circulating levels of C-reactive protein (CRP) and leukocytes in peripheral blood and fractional exhaled nitric oxide (FeNO). Proinflammatory cytokines interleukin (IL)-1β and IL-6 and tumor necrosis factor (TNF)-α were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 31 publications
1
32
2
1
Order By: Relevance
“…All statistical analyses were performed using the statistical software R, ). The present analyses had 78% power with 5% level of significance to detect an odds ratio of 3.1, as earlier reported in a cross-sectional study 12 comparing prevalence of high CRP among children living in homes with and without major moisture damage.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…All statistical analyses were performed using the statistical software R, ). The present analyses had 78% power with 5% level of significance to detect an odds ratio of 3.1, as earlier reported in a cross-sectional study 12 comparing prevalence of high CRP among children living in homes with and without major moisture damage.…”
Section: Discussionmentioning
confidence: 54%
“…17 In contrast to these results from prospective studies, cross-sectional study set among the same study subjects as with the present investigation found a significant association between major moisture damage in child's main living areas at 6 years of age and elevated circulating CRP levels at same age. 12 In addition, higher total fungal contamination in settled dust samples in Swedish day care centers assessed by quantitative PCR was significantly associated with elevated levels of CRP in 62 female teachers. 18 This suggests that immediate effects of exposure to moisture damage are more relevant in relation to systemic subclinical inflammation; however, the importance of early age exposure over a longer time period needs to be confirmed in larger study sets.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations